(3GdOQ GdfGLj Ydi EjSGZhLjs - (3GdoqJhbGOj GdajVj, YeQ Hf UGdM, J HYO (B1265 (3g`s ((3eMeO GdcGed Hf MSjf GdLfOj GdMhdGfjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj Ndb GdEfSGf hYdeg GdefWb hGdejRGf ajbhd GdSjO YeQ Hf UGdM GdJhbGOj gPg MhGT LOjOI Ydi eJf GjSGZhLj hSejJg GdOQ GdfGLjs
(3BNQgG (B:s
(3fNJe GdQSGdI HGdHQgGf dCfg GdehUd Edi GdSYGOI GdOjfjI hGdOfjhjI hGdefLj ef GdQOjI hGdaGFR HGdeWGdH GdSfjI hCeG Edi daX GdHQgGf jYfj GfbWY GdQSGdI hJe GdcdGe HdaX GdHQgGfs
(3aj BNQg agQSI JMaI QTOj TQM GjSGZhLjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 48s
(3eYLe GdeDdajf (B2 / 559s
(3EjVGM Gdecfhf (B1 / 452s
(3gOjI GdYGQajf (B1 / 800s
Keywords: (3GdadSaI hGdefWbs